2020
DOI: 10.3390/ani11010036
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation Forms Influenced Zinc Absorption and Accumulation in Piglets

Abstract: The study aimed at determining the effect of different zinc (Zn) supplementation forms on Zn accumulation, activities of Zn-containing enzymes, gene expression of metallothionein (MT), and Zn transporters in piglets. Eighteen piglets were randomly divided into three groups: (a) a basal diet supplemented with 150 mg/kg Zn from Zn methionine (Zn-Met) in the feed (Zn-Met group), (b) a basal diet supplemented with 150 mg/kg Zn from Zn sulfate (ZnSO4) in the feed (ZnSO4, feed group), and (c) a basal diet supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
3
4
2
Order By: Relevance
“…Contrary to the present study, Liu et al [23], Li et al [24] and Xie et al [25] reported ZnMet had no effect on ADG, ADFI, and FCR in weaned piglets. The discrepancies may be attributed to variations in the bioavailability of diverse amino acid-chelated zinc and differences in the types of diets consumed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the present study, Liu et al [23], Li et al [24] and Xie et al [25] reported ZnMet had no effect on ADG, ADFI, and FCR in weaned piglets. The discrepancies may be attributed to variations in the bioavailability of diverse amino acid-chelated zinc and differences in the types of diets consumed.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the supplementation of 75-100 mg/kg ZnVal showed a higher concentration of zinc in liver and dietary supplementation with 50-100 mg/kg ZnVal increased the concen-trations of zinc in the heart, spleen and kidney, indicating that the addition of ZnVal improved the absorption of trace elements. These results were partly in accordance with the results of Liu et al [23], who reported that dietary supplementation with 150 mg/kg ZnMet showed a higher concentration of zinc in liver in piglets. Furthermore, Zhang et al [43], reported that the supplementation of ZnMet to growing-nishing pigs signi cantly increased the concentrations of zinc in the muscle, liver, kidney and serum in comparison with the ZnSO 4 supplementation of growing-nishing pigs and Jahanian et al [44] found that incremental levels of ZnMet increased zinc concentrations in liver and thymus of broiler chicks.…”
Section: Discussionsupporting
confidence: 92%
“…qPCR was performed in a 10 μl reaction volume using a SYBR Premix Ex Taq kit (Takara, Japan). PCR amplification was performed according to a previous study ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that ZnMet had a higher bioavailability among zinc sources ( 41 ); therefore, we further detected the concentration of zinc in serum and tissues, which can reflect the absorption and utilization of zinc and is also used as an indicator to evaluate the nutritional status of the body ( 42 ). An increase in serum zinc concentration indicates that zinc metabolism is enhanced ( 43 ).…”
Section: Discussionmentioning
confidence: 99%